2012
DOI: 10.1016/j.pedhc.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Vulnerable Adolescents in a Pregnancy Prevention Program: Perspectives of Prime Time Staff

Abstract: Introduction Evaluating interventions for reducing unintended adolescent pregnancy is necessary to ensure quality and efficacy. The purpose of this study was to examine core case management practices and processes for engaging high-risk girls in Prime Time, an intensive multi-component intervention from the perspectives of intervention program staff. Method Structured individual interviews were conducted with the entire Prime Time program staff (N=7) to assess successes and challenges in engaging adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Together with previous findings demonstrating reductions in sexual risk behaviors, relational aggression, and violence victimization among Prime Time participants, 12-14,26 results from this study suggest that involvement in a youth development intervention that combines individualized case management and youth leadership components holds great promise for preventing multiple risk behaviors among youth most vulnerable to poor health outcomes, including early pregnancy. Furthermore, long-term increases in family connectedness as well as the beliefs and self-efficacy necessary to set healthy sexual boundaries suggest that interventions such as Prime Time may foster social and intrapersonal attributes needed to sustain healthy behaviors.…”
Section: Commentsupporting
confidence: 79%
See 1 more Smart Citation
“…Together with previous findings demonstrating reductions in sexual risk behaviors, relational aggression, and violence victimization among Prime Time participants, 12-14,26 results from this study suggest that involvement in a youth development intervention that combines individualized case management and youth leadership components holds great promise for preventing multiple risk behaviors among youth most vulnerable to poor health outcomes, including early pregnancy. Furthermore, long-term increases in family connectedness as well as the beliefs and self-efficacy necessary to set healthy sexual boundaries suggest that interventions such as Prime Time may foster social and intrapersonal attributes needed to sustain healthy behaviors.…”
Section: Commentsupporting
confidence: 79%
“…Details regarding case managers’ backgrounds, training, and supervision are found elsewhere as are intervention components, which are summarized here. 18,26 …”
Section: Methodsmentioning
confidence: 99%
“…Case managers completed an initial 4-week training focused on intervention principles, practice and feedback in implementing core intervention strategies. Case managers received weekly clinical supervision throughout the intervention, detailed elsewhere (Tanner et al 2012). Each intervention component is summarized below and described more fully elsewhere (Sieving et al 2011b).…”
Section: Methodsmentioning
confidence: 99%
“…Interviews with intervention staff indicated that within this vulnerable group there was considerable variability in girls’ initial interest and abilities to engage with case managers. Thus, case managers used distinct strategies to establish trusting relationships with girls who were easier or more difficult to engage (Tanner et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Building on our team’s ongoing expertise using social media, including Facebook, text messaging, and apps to promote HIV testing (Sun, et al, 2016; Sun, et al, 2015; Bachmann, et al, 2013; Rhodes, 2004; Rhodes, et al, 2011) as well as our research with youth and young adults with HIV (Tanner, et al, 2014; Tanner, et al, 2014; Tanner, et al, 2012; Tanner, 2008; Philbin, et al, 2014; Philbin, et al, 2014; Tanner, et al, 2014; Tanner, et al, 2013; Vissman, et al, 2011; Vissman, et al, 2013), we are in the development phase of a 4-year Health Resources and Services Administration (HRSA) funded project to design a social media intervention to improve care linkage and retention among underserved, underinsured, and hard-to-reach, racially and ethnically diverse young MSM with HIV. The purpose of this paper is to describe design and development of, weCare, our social media-based intervention to improve care linkage and retention and health outcomes among racially and ethnically diverse MSM, ages 13–34, living with HIV.…”
Section: Introductionmentioning
confidence: 99%